2018
DOI: 10.1002/nbm.4012
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism under different anesthetic conditions using hyperpolarized [1‐13C]pyruvate and [2‐13C]pyruvate

Abstract: Carbon-13 NMR spectroscopy (13C MRS) offers the unique capability to measure brain metabolic rates in vivo. Hyperpolarized 13C reduces the time required to assess brain metabolism from hours to minutes compared to conventional 13C MRS. This study investigates metabolism of hyperpolarized [1-13C]pyruvate and [2-13C]pyruvate in the rat brain in vivo under various anesthetics: pentobarbital, isoflurane, α-chloralose, and morphine. The apparent metabolic rate from pyruvate to lactate modeled using time courses obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…A recent HP 13 C MRS study with HP [1- 13 C] Pyr at different brain consciousness states demonstrated that the conversion rate of Pyr to bicarbonate is consistent with the TCA cycle rate determined from non-HP experiments and corresponds to what is expected under different anesthetic conditions [ 43 ]. However, when using HP [1- 13 C] Pyr, the conversion rates of Pyr to Lac did not change significantly under different anesthetic conditions [ 43 ]. HP Pyr experiments are capable to probe only a specific portion of the Glc metabolism.…”
Section: Discussionsupporting
confidence: 54%
“…A recent HP 13 C MRS study with HP [1- 13 C] Pyr at different brain consciousness states demonstrated that the conversion rate of Pyr to bicarbonate is consistent with the TCA cycle rate determined from non-HP experiments and corresponds to what is expected under different anesthetic conditions [ 43 ]. However, when using HP [1- 13 C] Pyr, the conversion rates of Pyr to Lac did not change significantly under different anesthetic conditions [ 43 ]. HP Pyr experiments are capable to probe only a specific portion of the Glc metabolism.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, confounding factors concerning in vivo rodent experiments involve the blood-brain-barrier (BBB) transport kinetics via monocarboxylate transporters, 52 and their dependence on the anesthesia used. 21,26,28 Ex vivo, the BBB is severed and thus the arrival of hyperpolarized [1- 13 C] pyruvate to the cells is likely faster, as is the case for a disturbed BBB in vivo. 34 In a previous study using a similar ex vivo preparation we used a conventional small flip angle acquisition approach to collect the data.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,14 Hyperpolarized [1- 13 C]pyruvate has been previously used to observe rapid metabolic processes in many promising applications. [16][17][18][19] Specifically, real-time brain metabolism was investigated in vivo in small animals [20][21][22][23][24][25][26][27][28][29][30] and, relating to stroke, 31,32 in the human brain 10,[33][34][35][36] and in the rat brain ex vivo. 5 In the current study, hyperpolarized [1- 13 C]pyruvate was also used as the metabolic substrate.…”
mentioning
confidence: 99%
“…Hyperpolarized [1- 13 C]pyruvate has been previously used to observe rapid metabolic processes in many promising applications [ 27 , 28 , 29 , 30 ]. Specifically, real-time brain metabolism was investigated in vivo in small animals [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], in small animal models related to stroke [ 42 , 43 ], in the human brain [ 25 , 44 , 45 ], and in the rat brain ex vivo [ 46 ].…”
Section: Introductionmentioning
confidence: 99%